STABILISASI TANAH MENGGUNAKAN KAOLIN DAN KAPUR (STUDI KASUS TANAH RESIDUAL DI AREA STT-PLN DURI KOSAMBI JAKARTA BARAT) - Indah Handayasari (Sekolah Tinggi Teknik - PLN, 2016)
The topography of West Jakarta area categorized as flat and sloping areas with characteristics of the soil and rock is generally a silty sand, sandy loam, silt loam and sandy silt. Soil conditions in this category have a relatively low carrying capacity and the potential development of a large shrinkage. Carrying capacity of the land itself is one of the parameters on both the construction work under the structure and the upper structure. If the soil does not have a good carrying capacity it will be very dangerous constructions built upon. One improvement to get the soil bearing capacity to be expected that the chemical soil stabilization methods. One chemical soil remediation efforts can be done by adding a siliceous material such as kaolin and limestone soil residual material in West Jakarta area. The research sample was made with kaolin and limestone composition ratio of the residual soil with a treatment that is 0%, 5%, 10%, and 15% of the dry weight of residual soil. Ripening soil mix made for 1 day, 7 days and 14 days. From the test results obtained optimum value on the ground with a mixture of 10% lime and 10% kaolin with a long ripening 14 days. Where the soil with a mixture of 10% lime and 10% kaolin with a long ripening 14 days had a specific gravity is 1.8944, 53.7865% liquid limit, plastic limit 0.4856% 23.3009% plasticity index, shrinkage limit 38.92321% , CBR value of 195.6898%, the cohesion of 0,6767 kg/cm2, and the value of the friction angle of 39°52'44''.